Psikologi Pendidikan Islam Di Era Digital: Tantangan Dan Solusi - Puspitasari, Rini; Mindani, Mindani; Anshori, Muhammad Farouk Alakbar; Aprisa, Melda Tri; Malasari, Junita; Khoirunnisa, azizah (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
This study examines the challenges and solutions of Islamic educational psychology in the digital age, focusing on three core issues: digital distraction, exposure to negative content, and limited teacher digital literacy. Through qualitative literature review and thematic content analysis, the research identifies that gadget addiction and social media/gaming platforms disrupt students' learning focus, moral development, and mental health, contradicting Islamic principles like the preservation of al-'aql (intellect). Educators' unpreparedness to integrate technology with Islamic values further hinders faith-based learning effectiveness. Proposed solutions include: (1) Developing Islamic-based technological platforms (e.g.,